1983
DOI: 10.1126/science.6857249
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions in Collagen Self-Assembly as Revealed by Fourier Transform Infrared Spectroscopy

Abstract: When a solution of collagen molecules, at neutral pH and moderate ionic strength, is warmed from 4 degrees to 30 degrees C, a spontaneous self-assembly process takes place in which native-type collagen fibers are produced. Events occurring during thermally induced fibrillogenesis process can be monitored, in aqueous media and in real time, by Fourier transform infrared spectroscopic techniques. Tentative assignments of observed spectral bands are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 12 publications
7
30
0
Order By: Relevance
“…The frequency of the amide II peak also decreased. This trend was similar to that seen in a previous study in which the amide peak frequency downshift was observed when full-length collagen forms fibrils by increasing the temperature of the collagen solution, [26] suggesting that the film formed by slow evaporation of NATCOL peptide solution contained similar collagen fibrillar structure. However, no changes in the position of Amide I peak were observed for films formed from NATCOL by fast evaporation, indicating fast evaporation tends to prevent formation of ordered phases.…”
Section: Fourier Transformed Infrared Spectroscopysupporting
confidence: 87%
“…The frequency of the amide II peak also decreased. This trend was similar to that seen in a previous study in which the amide peak frequency downshift was observed when full-length collagen forms fibrils by increasing the temperature of the collagen solution, [26] suggesting that the film formed by slow evaporation of NATCOL peptide solution contained similar collagen fibrillar structure. However, no changes in the position of Amide I peak were observed for films formed from NATCOL by fast evaporation, indicating fast evaporation tends to prevent formation of ordered phases.…”
Section: Fourier Transformed Infrared Spectroscopysupporting
confidence: 87%
“…These amide bands are considered to be signatures which characterize peptide conformation. [16] Despite the general similarities, the spectra for the two types of fibrils exhibit some differences. The observed differences are mostly manifested in the positions of the characteristic amide bands.…”
Section: Resultsmentioning
confidence: 99%
“…18,23,24 Therefore, these spectral alterations together with the reduced amide III band in this study represented the imposed molecular interactions of Chi on Col, including depression of hydrogen bonding of Col self assembly and forming complexes with Col. However, the complete denaturation of Col did not occur in this study.…”
mentioning
confidence: 96%